PEDAGOGICAL ASPECTS OF PREPARATION FOR MILITARY SERVICE OF SENIOR SECONDARY SCHOOL STUDENTS (American Journal of Interdisciplinary Research and Development, 2024)
The preparation of senior secondary school students for military service involves a multi-faceted pedagogical approach that integrates physical, psychological, and educational components. This article explores the essential pedagogical aspects that contribute to the effective preparation of students for military service, emphasizing curriculum design, teaching methodologies, and the development of essential skills and attitudes.